Case report: MRI findings with CNS blastomycosis in three domestic cats - Hecht, Silke; Michaels, Jennifer R.; Simon, Heather (Frontiers in Veterinary Science, 2022)
Blastomycosis is a systemic mycotic infection caused by dimorphic fungi. The disease is rare in cats, and reports on imaging findings with central nervous system (CNS) involvement are limited. Magnetic resonance imaging (MRI) was performed antemortem in three feline patients. Imaging findings which may allow prioritization of intracranial blastomycosis over other differential diagnoses included focal or multifocal intra-axial mass lesions with dural contact, lesion hypointensity on T2-weighted images and diffusion weighted imaging/apparent diffusion coefficient map (DWI/ADC), strong and homogeneous contrast enhancement of the lesion(s), concurrent meningeal enhancement, marked perilesional edema and mass-effect, and ocular abnormalities. One cat was managed successfully and had recurrence of CNS blastomycosis more than 4.5 years after the initial diagnosis. Repeat MRI at that point revealed both new and persistent (chronic) abnormalities.